Dupilumab Efficacy and Safety in Severe Atopic Dermatitis in Children under 6 Years of Age: Two Clinical Cases - Nikolay N. Murashkin; Leonid A. Opryatin; Ekaterina S. Pavlova; Roman V. Epishev; Alexandr I. Materikin; Roman A. Ivanov; Alena A. Savelova; Maria A. Leonova ("Paediatrician" Publishers LLC, 2023)
Background. Atopic dermatitis (AD) manifests during the first year of life in majority of all cases. The early disease onset is associated with the development of comorbid atopic conditions within the «atopic march» phenomenon. The AD pathogenesis is associated with genetic predisposition, epidermal barrier dysfunction, and immune dysregulation. T2-inflammation specifically determines the entire immune cascade of inflammatory reactions, and, thus, dictates the need of early drug intervention to modify the disease course. Clinical case description. This article presents two clinical cases of severe AD in children under 6 years of age. The treatment of both cases included genetically engineered biologic drug dupilumab. Continuous therapy for 4-5 months made it possible to relieve the skin manifestations of the disease.Conclusion. AD, manifesting in infancy, is associated with high risk of developing other atopic spectrum diseases in older age. The timely onset of biological therapy allows us to affect immune dysregulation, and thereby to prevent the comorbid atopic conditions development.